Dynamics analysis of underwater glider based on fluid-multibody coupling model. (15th June 2023) - Wang, Haibo; Chen, Junsi; Feng, Zhanxia; Li, Yuze; Deng, Chao; Chang, Zongyu
Abstract: The underwater glider is a kind of underwater mobile platform, which can carry different sensors to detect multiple targets in the ocean. In the dynamics analysis of underwater gliders, the hydrodynamic forces on the airfoil are generally calculated by empirical formulas and hydrodynamic ratios, ignoring the interaction between the glider and the fluid. In this paper, a fluid-multibody coupling method integrating the multibody dynamic model and the fluid dynamic model is proposed to calculate the dynamic characteristics, such as pitch angle and horizontal propulsion. Meanwhile, the effects of the net buoyancy mass and the displacement of internal moving mass on the dynamic characteristics and wake vortex of underwater gliders at different motion phases are analyzed. Thanks to the consideration of the interaction between multibody dynamics and hydrodynamics, the proposed fluid-multibody coupling model provides a new approach to analyzing the dynamic response of the glider, guiding the design and control of the underwater glider. Highlights: A fluid-multi-body coupling method combines multi-body dynamics model and hydrodynamic model to analyze the dynamical response of an underwater glider. A fluid-multibody coupling method takes the real-time interaction between the glider and the surrounding flow field into account. A fluid-multibody coupling model obtains the dynamic response and the implicit effects of the internal mass and displacement on the gliding speed, attitude and force.